DNA profiling with the 20K apple SNP array reveals Malus domestica hybridization and admixture in M. sieversii, M. orientalis, and M. sylvestris genebank accessions - Volk, Gayle M.; Peace, Cameron P.; Henk, Adam D.; Howard, Nicholas P. (Frontiers in Plant Science, 2022)
The USDA-ARS National Plant Germplasm System (NPGS) apple collection in Geneva, NY, USA maintains accessions of the primary Malus domestica (Suckow) Borkh. progenitor species M. sieversii (Ledeb.) M. Roem., M. orientalis Uglitzk., and M. sylvestris (L.) Mill. Many of these accessions originated from seeds that were collected from wild populations in the species’ centers of diversity. Some of these accessions have fruit phenotypes that suggest recent M. domestica hybridization, which if true would represent crop contamination of wild species populations and mislabeled species status of NPGS accessions. Pedigree connections and admixture between M. domestica and its progenitor species can be readily identified with apple SNP array data, despite such arrays not being designed for these purposes. To investigate species purity, most (463 accessions) of the NPGS accessions labeled as these three progenitor species were genotyped using the 20K apple SNP array. DNA profiles obtained were compared with a dataset of more than 5000 unique M. domestica apple cultivars. Only 212 accessions (151 M. sieversii, 26 M. orientalis, and 35 M. sylvestris) were identified as “pure” species representatives because their DNA profiles did not exhibit genotypic signatures of recent hybridization with M. domestica. Twenty-one accessions (17 M. sieversii, 1 M. orientalis, and 3 M. sylvestris) previously labeled as wild species were instead fully M. domestica. Previously unrealized hybridization and admixture between wild species and M. domestica was identified in 230 accessions (215 M. sieversii, 9 M. orientalis, and 6 M. sylvestris). Among these species-mislabeled accessions, ‘Alexander’, ‘Gold Reinette’, ‘Charlamoff’, ‘Rosmarina Bianca’, and ‘King of the Pippins’ were the most frequently detected M. domestica parents or grandparents. These results have implications for collection management, including germplasm distribution, and might affect conclusions of previous research focused on these three progenitor species in the NPGS apple collection. Specifically, accessions received from the NPGS for breeding and genomics, genetics, and evolutionary biology research might not be truly representative of their previously assigned species.